Prospect of robotic assistance for fully automated brachytherapy seed placement into skull base: Experimental validation in phantom and cadaver. (February 2019) - Zhu, Jian-Hua; Wang, Jing; Wang, Yong-Gui; Li, Meng; Liu, Xiao-Jing; Guo, Chuan-Bin
Abstract: Background and purpose: To investigate the feasibility and accuracy of robot-assisted brachytherapy for skull base tumours. Material and methods: A custom robot system was tested on both phantom and cadaveric specimen. Cone beam CT (CBCT) images were transferred to the graphical user interface (GUI) for planning trajectories and the data were sent to the robot control unit. Following registration, the puncture needle was inserted into the target by the robot under navigation guidance, and seeds were implanted. Placement error was instantly displayed on the GUI; the result was verified after postoperative image scanning. Results: A total of 150 seeds (100 for phantom experiments, 50 for cadaveric studies) were deposited by the robot system. In phantom experiments the mean placement error was 0.57 ± 0.21 mm (measured by the navigation system) vs. 1.41 ± 0.38 mm (measured by image fusion) ( p  < 0.001); in cadaveric studies the corresponding figures were 0.60 ± 0.30 mm vs. 2.48 ± 0.32 mm ( p  < 0.001). There was no significant difference for comparison of accuracy test in phantom experiments ( p  = 0.173) as well as in cadaveric studies ( p  = 0.354). Accuracy was better in the phantom experiment than in cadaveric studies ( p  < 0.001). Conclusions: The performance of robot-assisted skull base brachytherapy is feasible and accurate. Dosimetric coverage will need to be demonstrated in further studies.